Mali : Sixth Review Under the Extended Credit Facility Arrangement and Request for Modification of a Performance Criterion-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses Mali's Sixth Review Under the Extended Credit Facility Arrangement and Request for Modification of a Performance Criterion. Economic activity in Mali remains robust, aided both by higher public investment and accommodative monetary conditions. Inflation remains subdued, helped by favorable weather conditions and low global inflation. The external position has weakened, reflecting strong domestic demand growth, but is expected to strengthen in the near term as terms of trade improve and demand growth slows down. The near-term outlook remains positive but is subject to downside risks, stemming mainly from the fragile security conditions.